Evidence-informed recommendations for rehabilitation with older adults living with HIV: a knowledge synthesis. Issue 5 (14th May 2014) - O'Brien, Kelly K; Solomon, Patricia; Trentham, Barry; MacLachlan, Duncan; MacDermid, Joy; Tynan, Anne-Marie; Baxter, Larry; Casey, Alan; Chegwidden, William; Robinson, Greg; Tran, Todd; Wu, Janet; et al.
Abstract : Objective: Our aim was to develop evidence-informed recommendations for rehabilitation with older adults living with HIV. Design: We conducted a knowledge synthesis, combining research evidence specific to HIV, rehabilitation and ageing, with evidence on rehabilitation interventions for common comorbidities experienced by older adults with HIV. Methods: We included highly relevant HIV-specific research addressing rehabilitation and ageing (stream A) and high-quality evidence on the effectiveness of rehabilitation interventions for common comorbidities experienced by older adults ageing with HIV (stream B). We extracted and synthesised relevant data from the evidence to draft evidence-informed recommendations for rehabilitation. Draft recommendations were refined based on people living with HIV (PLHIV) and clinician experience, values and preferences, reviewed by an interprofessional team for Grading of Recommendations Assessment, Development, and Evaluation (GRADE) (quality) rating and revision and then circulated to PLHIV and clinicians for external endorsement and final refinement. We then devised overarching recommendations to broadly guide rehabilitation with older adults living with HIV. Results: This synthesis yielded 8 overarching and 52 specific recommendations. Thirty-six specific recommendations were derived from 108 moderate-level or high-level research articles (meta-analyses and systematic reviews) that described the effectiveness of rehabilitation interventions for comorbidities that may be experienced by older adults with HIV. Recommendations addressed rehabilitation interventions across eight health conditions: bone and joint disorders, cancer, stroke, cardiovascular disease, mental health challenges, cognitive impairments, chronic obstructive pulmonary disease and diabetes. Sixteen specific recommendations were derived from 42 research articles specific to rehabilitation with older adults with HIV. The quality of evidence from which these recommendations were derived was either low or very low, consisting primarily of narrative reviews or descriptive studies with small sample sizes. Recommendations addressed approaches to rehabilitation assessment and interventions, and contextual factors to consider for rehabilitation with older adults living with HIV. Conclusions: These evidence-informed recommendations provide a guide for rehabilitation with older adults living with HIV.